The effect of the Problem Based Learning (PBL) Learning Model on Students' Biology Learning Outcomes in the Ecosystem Material of Class X SMA Negeri 1 Purba, Simalungun Regency - Anastasya Sitanggang; Erlintan Sinaga (Florea : Jurnal Biologi dan Pembelajarannya, 2025)
This study aims to determine the effect of the Problem Based Learning learning model on student learning outcomes in the Ecosystem material at SMA Negeri 1 Purba, Simalungun Regency. This type of research is a quasi-experiment with a Pretest Posttest Only Control Group Design research design. The population of this study was all students of class X of SMA Negeri 1 Purba which consists of 6 classes. The research sample was 66 people, namely class X-2 as an experimental class with Problem Based Learning learning models and class X-5 as a control class with conventional learning. Data were obtained with a test instrument totaling 30 questions that had been validated by the validator. The results of the study showed that there was an effect of the Problem Based Learning model on student learning outcomes. The results of the study on learning outcomes using the t-test (independent sample t-test) showed that the significant value (sig 2-tailed) <0.05, namely the sig value of 0,000 < 0.05 so that Ha was accepted. Based on the research results, it can be concluded that there is an influence of the Problem Based Learning learning model on student learning outcomes in the Ecosystem material in Class X of SMA Negeri 1 Purba Simalungun Regency.